2H‐Tetrakis(3, 5‐di‐tert‐butyl)phenylporphyrin on a Cu(110) Surface: Room‐Temperature Self‐Metalation and Surface‐Reconstruction‐Facilitated Self‐Assembly. Issue 10 (2nd February 2016) - Zhang, Liang; Lepper, Michael; Stark, Michael; Schuster, Ralf; Lungerich, Dominik; Jux, Norbert; Steinrück, Hans‐Peter; Marbach, Hubertus
Abstract: The adsorption behavior of 2 H ‐tetrakis(3, 5‐di‐ tert ‐butyl)phenylporphyrin (2HTTBPP) on Cu(110) and Cu(110)–(2×1)O surfaces have been investigated by using variable‐temperature scanning tunneling microscopy (STM) under ultrahigh vacuum conditions. On the bare Cu(110) surface, individual 2HTTBPP molecules are observed. These molecules are immobilized on the surface with a particular orientation with respect to the crystallographic directions of the Cu(110) surface and do not form supramolecular aggregates up to full monolayer coverage. In contrast, a chiral supramolecular structure is formed on the Cu(110)–(2×1)O surface, which is stabilized by van der Waals interactions between the tert ‐butyl groups of neighboring molecules. These findings are explained by weakened molecule–substrate interactions on the Cu(110)–(2×1)O surface relative to the bare Cu(110) surface. By comparison with the corresponding results of Cu–tetrakis(3, 5‐di‐ tert ‐butyl)phenylporphyrin (CuTTBPP) on Cu(110) and Cu(110)–(2×1)O surfaces, we find that the 2HTTBPP molecules can self‐metalate on both surfaces with copper atoms from the substrate at room temperature (RT). The possible origins of the self‐metalation reaction at RT are discussed. Finally, peculiar irreversible temperature‐dependent switching of the intramolecular conformations of the investigated molecules on the Cu(110) surface was observed and interpreted. Abstract : Role of the substrate : 2 H ‐Tetrakis(3, 5‐di‐ tert ‐butyl)phenylporphyrin (2HTTBPP) molecules can self‐metalate with copper atoms from the substrate on both Cu(110) and Cu(110)–(2×1)O surfaces at room temperature (RT; see figure). The (2×1) surface reconstruction of Cu(110) by oxygen atoms also significantly modifies the molecule–substrate interaction and facilitates the self‐assembly of 2HTTBPP molecules at RT.